Evaluation of the Stability of the Total Antioxidant Capacity, Polyphenol Contents, and Starch Hydrolase Inhibitory Activities of Kombucha Teas Using an In Vitro Model of Digestion - Mindani I. Watawana; Nilakshi Jayawardena; Shakkya J. Ranasinghe; Viduranga Y. Waisundara (Journal of Chemistry)
The objective of this study was to evaluate and compare antioxidant and starch hydrolase inhibitory activity of three different types of Kombucha beverages prepared by three pellicles with different microbial compositions. The fermentation process was carried out for 7 days and the assessments of antioxidant and starch hydrolase inhibitory activities as well as tea phenolic compounds were carried out. These parameters were also evaluated after subjecting the final fermented samples to gastric and duodenal digestion in an in vitro digestion model. The pH had a statistically significant decrease during the period of fermentation. The total phenolics content and antioxidant activities had increased during the fermentation process as well as when subjected to digestion. The starch hydrolase inhibitory activities also increased in a similar manner during the different phases. The α-amylase and α-glucosidase inhibitory activities showed statistically significant increases (P<0.05) as the fermentation progressed, while an increase was observed after being subjected to pancreatic and duodenal digestion as well. All three types of tea showed a higher α-amylase inhibitory activity than α-glucosidase inhibitory activity.